2012
DOI: 10.1111/tpj.12063
|View full text |Cite
|
Sign up to set email alerts
|

The tomato cis–prenyltransferase gene family

Abstract: SUMMARYcis-prenyltransferases (CPTs) are predicted to be involved in the synthesis of long-chain polyisoprenoids, all with five or more isoprene (C5) units. Recently, we identified a short-chain CPT, neryl diphosphate synthase (NDPS1), in tomato (Solanum lycopersicum). Here, we searched the tomato genome and identified and characterized its entire CPT gene family, which comprises seven members (SlCPT1-7, with NDPS1 designated as SlCPT1). Six of the SlCPT genes encode proteins with N-terminal targeting sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
138
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 59 publications
(97 reference statements)
1
138
1
3
Order By: Relevance
“…RNA was isolated according to the manufacturer's protocol. First strand cDNA was synthesized using SuperScript III reverse transcriptase (Invitrogen) and oligo(dT) [12][13][14][15][16][17][18] primer (Invitrogen) using 1-5 g of total RNA. Quantitative real time PCR (qRT-PCR) was performed (Step One Real-Time PCR System; Applied Biosystems, Carlsbad, CA) using Power SYBER Green PCR Master Mix (Applied Biosystems), 5 M primer, and cDNA template (equivalent to 5 ng of total RNA) in a reaction volume of 10 l. The qRT-PCR program was 1 cycle of 95°C for 10 min and 40 cycles of 95°C for 15 s and 58°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was isolated according to the manufacturer's protocol. First strand cDNA was synthesized using SuperScript III reverse transcriptase (Invitrogen) and oligo(dT) [12][13][14][15][16][17][18] primer (Invitrogen) using 1-5 g of total RNA. Quantitative real time PCR (qRT-PCR) was performed (Step One Real-Time PCR System; Applied Biosystems, Carlsbad, CA) using Power SYBER Green PCR Master Mix (Applied Biosystems), 5 M primer, and cDNA template (equivalent to 5 ng of total RNA) in a reaction volume of 10 l. The qRT-PCR program was 1 cycle of 95°C for 10 min and 40 cycles of 95°C for 15 s and 58°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Null mutations of E. coli UPPS and double knock-out of the two yeast CPTs are lethal, confirming that they are essential genes (9,11). In plants, studies of well annotated genomes showed that multiple copies of CPTs are present (12,13), but the exact physiological role of each CPT is not fully understood.…”
mentioning
confidence: 99%
“…We recently showed that the promoter of ShMKS1 is highly active in type VI trichomes of cultivated tomato ( Akhtar et al, 2013). To test the activity of the ShMKS2 promoter in cultivated tomato, we made a construct that fused the 1.5-kb upstream region of ShMKS2 with GFP and transformed cultivated tomato plants.…”
Section: Production Of Transgenic Tomato Plants With Trichome-specifimentioning
confidence: 99%
“…ShMKS1 and ShMKS2 are specifically expressed in the gland cells of type VI trichomes in wild tomato, and both proteins are targeted to the plastids (Yu et al, 2010;Akhtar et al, 2013;G. Yu, A.L.…”
mentioning
confidence: 99%
“…CPTs are not homologous to trans-prenyldiphosphate synthases, and comparatively little is known about these enzymes, particularly in plants. Bioinformatic analysis indicates that animal and prokaryotic genomes typically encode a single CPT, while plants maintain small CPT gene families, containing anywhere between three to nine members (Surmacz and Swiezewska, 2011;Akhtar et al, 2013). Bacterial CPTs synthesize the Pren-11 (C55) polyprenol known as undecaprenyl diphosphate, which as mentioned above, functions in peptidoglycan biosynthesis, while animal CPTs are involved in the synthesis of longer chain dolichols that serve an indispensable role in protein N-glycosylation.…”
Section: Introductionmentioning
confidence: 99%